Categorising Syrians in Lebanon as ‘vulnerable’ - Maja Janmyr; Lama Mourad (Forced Migration Review, 2018)
Vulnerability assessments are used by humanitarian actors to identify those at greater risk of harm but their use in the response to displaced Syrians in Lebanon is problematic.